2017
DOI: 10.22158/selt.v5n4p695
|View full text |Cite
|
Sign up to set email alerts
|

EFL Teachers’ Challenges in Maximizing Classroom Interaction

Abstract: Classroom interaction plays a significant role in facilitating learners' development of communicative competence by making input more comprehensible to learners and maximizing the language input to become learners' intake (Krashen, 1987;Swain, 1995;Long, 1996;Gass, 1997;Lucha & Berhanu, 2015). Results of related studies reveal a low level of communicative competence of many Vietnamese learners of English, which could result from the lack of opportunities for interaction in Vietnamese EFLclasses (Hiep, 2007; Ng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…In contrast, heterogeneous groupings are favored during task discussions to facilitate peer support and foster teacher-student relationships (Lai, 2011).…”
Section: Responses Towards Flexible Grouping Strategiesmentioning
confidence: 99%
“…In contrast, heterogeneous groupings are favored during task discussions to facilitate peer support and foster teacher-student relationships (Lai, 2011).…”
Section: Responses Towards Flexible Grouping Strategiesmentioning
confidence: 99%
“…Their findings also indicated that most of the students never or rarely participated in EFL classroom oral interactions. Another study conducted by Lap and Thy (2017) entitled, "EFL instructors' challenges in maximizing classroom interaction" found out that Vietnamese EFL lecturers encountered challenges related to physical factors, learners' factors, and teachers' factors. As a result, learners were not able to communicate effectively in speaking in the target language after years of learning it.…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…Because this instructional approach is very content-focused, teachers educate by simply transmitting and imparting knowledge to students who are expected to have passively absorbed the material. This then results to failure of developing communicative competence and mastery of the content due to minimal oral discourse engagement (Lap and Thy, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%